Diagnosis and Management of Enthesopathy - Hafiziani; Najirman (HM Publisher, 2022)
Enthesopathy is inflammation of the enthesis. Outcome Measures in Rheumatologic Clinical Trials (OMERACT) defined enthesopathy as abnormal hypoechoic (loss of normal fibrillar architecture) and/or tendon or ligament thickening at the site of bone attachment (sometimes containing hyperechoic foci that resemble calcifications) seen in two perpendicular planes on Doppler and/or bony changes including ensophytes, erosions, and irregularities. The causes of enthesopathy are categorized into two, namely, non-inflammatory causes and inflammatory causes. Non-inflammatory causes include trauma, degenerative, autoimmune, genetic, and metabolic. The causes of inflammation areas in seronegative spondyloarthropathy.